Патріотичне виховання студентів ВТНЗ на заняттях з соціально-гуманітарних дисциплін - Абрамчук, О. В. (НТУ "ХПІ", 2016)
У статті йдеться про патріотичне виховання майбутніх інженерів засобами соціально-гуманітарних дисциплін. Дається коротка характеристика змісту навчальних дисциплін: української мови, історії України, історії культури України, соціології. Увага приділяється відповідності змісту дисциплін навчальній та виховній меті навчально-виховного процесу.

The article refers to the patriotic education of future engineers by means of social and human sciences. We give a brief description of the content of such subjects as: Ukrainian language, history of Ukraine, history of Ukraine's culture, sociology. Attention is given to the correspondence of academic disciplines to educational purpose of the educational process.
Patriotic education of technical university students at the humanities lessons
Keywords: виховні можливості; національна свідомість; народні традиції; українська ідея; культура мовлення; educational opportunities; national consciousness; national traditions